Comparative chemical composition, antioxidant and anticoagulant properties of phenolic fraction (a rich in non-acylated and acylated flavonoids and non-polar compounds) and non-polar fraction from Elaeagnus rhamnoides (L.) A. Nelson fruits. (1st May 2018) - Olas, Beata; Żuchowski, Jerzy; Lis, Bernadetta; Skalski, Bartosz; Kontek, Bogdan; Grabarczyk, Łukasz; Stochmal, Anna
Highlights: The phenolic and non-polar fractions of the fruit were investigated. The phenolic fraction was rich in flavonoids, the non-polar one – in triterpenes. Both fractions inhibited H2 O2 -induced lipid peroxidation in human plasma. The non-polar fraction inhibited H2 O2 /Fe-induced lipid peroxidation in human plasma. Both fractions decreased H2 O2 /Fe-induced protein carbonylation in human plasma. Abstract: This study focuses on two fractions from sea buckthorn ( Elaeagnus rhamnoides (L.) A. Nelson) fruits: the phenolic fraction (rich in non-acylated and acylated flavonoids and non-polar compounds) and the non-polar fraction. The objective was to investigate both the chemical composition of these fractions, as well as their biological activities in vitro . The tested fractions of sea buckthorn inhibited lipid peroxidation induced by H2 O2, however, the non-polar fraction reduced more powerfully the process induced by H2 O2 /Fe as compared to the phenolic fraction. The tested fractions of sea buckthorn fruits also inhibited carbonylation stimulated by H2 O2 /Fe. Moreover, the action of the phenolic fraction and non-polar fraction on hemostatic parameters of plasma was also compared to activities of other phenolic fraction, in which flavonoids were the dominant compounds. Our results indicate that sea buckthorn fruits are a rich source of different secondary metabolites, i.e. triterpenes and their derivates, which possess not only antioxidant properties, but may also display anticoagulant attributes.